The river of time - Probštejn, Jan Ėmilʹevič (Academic Studies Press, 2017)
Introduction. Forms of time-space (chronotope) in poetry – Beyond barriers: avant-garde and futurism – Forms of chronotope in avant-garde poetry –
Literaturverzeichnis Seite 245-265
Keywords: Space and time in literature; History in literature; Russisch; Raum-Zeit; Lyrik; Literatur; Moderne; Englisch